Maple leaf-based triboelectric nanogenerator for efficient energy harvesting and precision monitoring in ping-pong training - He Yu; Zheng Li (AIP Advances)
Triboelectric technology, with its renewable, low-cost, and eco-friendly advantages, offers new possibilities for intelligent motion-sensing equipment and sports monitoring. We propose a maple leaf-based triboelectric nanogenerator (ML-TENG) for green mechanical energy harvesting and detecting table tennis corner kicks. The ML-TENG operates in contact-separation mode and achieves a peak power output of 63.38 W/m3 at an optimal load of 50 MΩ. The experimental results show a transfer charge (Qsc) of 35 nC, a short-circuit current (Isc) of 9 μA, and an open-circuit voltage (Voc) of 50 V. Tested with a ping-pong paddle, the ML-TENG generates consistent voltage even under high-frequency impacts, demonstrating its sensitivity to both strong and weak forces. This ready-to-use design requires minimal preparation, highlighting triboelectric technology’s potential for improving sports monitoring accuracy and enabling real-time athletic performance analysis.